Tardigrade distribution in soils of high Arctic habitats - Michala Tůmová; Veronika Jílková; Petr Macek; Miloslav Devetter (Ecology and Evolution)
Abstract Tardigrades are omnipresent microfauna with scarce record on their ecology in soils. Here, we investigated soil inhabiting tardigrade communities in five contrasting polar habitats, evaluating their abundance, diversity, species richness, and species composition. Moreover, we measured selected soil physico‐chemical properties to find the drivers of tardigrade distribution among these habitats. In spite of reported tardigrade viability in extreme conditions, glacier forelands represented a habitat almost devoid of tardigrades. Even dry and wet tundra with soil developing for over more than 10 000 years held low abundances compared to usual numbers of tardigrades in temperate habitats. Polar habitats also differ in species composition, with Diaforobiotus islandicus being typical species for dry and Hypsibius exemplaris for wet tundra. Overall, tardigrade abundance was affected by the content of nutrients as well as physical properties of soil, i.e. content of total nitrogen (TN), total organic carbon (TOC), stoniness, soil texture and the water holding capacity (WHC). While diversity and species composition were significantly related to soil physical properties such as the bulk density (BD), soil texture, stoniness, and WHC. Physical structure of environment was, therefore, an important predictor of tardigrade distribution in polar habitats. Since many studies failed to identify significant determinants of tardigrade distribution, we encourage scientists to include physical properties of tardigrade habitats as explanatory variables in their studies.